Pengaruh Kompetensi dan Motivasi Terhadap Kualitas Audit APIP dengan Independensi Sebagai Variabel Moderating (Studi Pada Inspektorat Provinsi Sumatera Utara) - K Khairunita (Universitas Islam Negeri Sumatera Utara, 2020)
This research aims to exmine the effect of competence on audit quality, examine the effect of motivation on audit quality, examine the effect of competence and motivation on audit quality, testing independence can moderate the effect of competence on audit quality, testing independence can moderate the effect of motivation on audit quality. The object of this research is the North Sumatra Province Inspectorate Office. The sample in this study was50 (fifty) auditors and supervisors at the North sumatra Utara Province Inspectorate Office. Data collection is carried out by means of the questionnaire method. The method used is multiple linier regression analysis and MRA (Moderating Regression Analysis). The result of this study indicate that there is an effect of competence on audit quality, there is a motivational effect on audit quality, there is an influence of competence and motivation on audit quality, independence moderates the effect of competence on audit quality, independence moderates the effect of motivation on audit quality.